THE RELIABILITY OF FOREIGN LANGUAGE ANXIETY SCALE IN MALAY VERSION BASED ON CRONBACH’S ALPHA - Rosnah Mohd. Sham; Mohd Nazri Latiff Azmi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
This paper is part of a study which addresses the reliability of Foreign Language Anxiety Scale (FLCAS) in Malay version.  Researchers find that the reliability of an instrument is closely associated with its validity and an instrument cannot be valid unless it is reliable. However, the reliability of an instrument does not depend on its validity. Therefore, this paper investigates the reliability of the instrument called FLCAS in Malay version.  FLCAS is widely used in collecting data relating to language anxiety and perhaps the most reliable and comprehensive tool in language anxiety.  This paper objectively measures the reliability of FLCAS by using Cronbach’s Alpha, the most widely used objective measure of reliability.  The sampled population involved 302 respondents from the government secondary schools in Putrajaya Federal Territory, Malaysia.  The items had been translated into the Malay language and back translated into English.  Results show that the internal consistency of Crobanch’s Alpha 0.90.  It can be concluded that FLCAS in Malay version is an appropriate instrument to measure the levels of language anxiety among the Malaysian secondary school students who learn English as a second language.